Implementasi Perencanaan Jalur menggunakan Algoritma Dijkstra pada Robot Roda Mecanum - Prayoga, Senanjung; Ompu Sunggu, Elmaria (Politeknik Negeri Batam, 2024)
This research develops a robot capable of moving from a starting point to a destination as well as avoiding collisions using Dijkstra's algorithm, which is effective in finding the shortest path. This algorithm is implemented on a mecanum robot equipped with an Arduino microcontroller, mini PC, battery, DC motor with encoder, motor driver, and related software. This study tested five maps with the same starting point and destination, but with different obstacle locations. The test results showed that the mecanum robot managed to find the path and avoid obstacles well. With an average maximum speed of 2.6 m/s, the robot can cover a distance of 3.2 meters without obstacles in 14.96 seconds, and a distance of 4.2 meters with obstacles in 22.82 seconds. This research demonstrates the potential of Dijkstra's algorithm in path planning and robot navigation, and underscores the importance of using the right hardware and software to achieve optimal performance. These results can serve as a basis for further development in the field of robotics, particularly in the application of autonomous robots in dynamic environments.